Productivity of ranch N'Dama cattle under trypanosomiasis risk - Feron, A.; D'Ieteren, G.D.M.; Durkin, J.W.; Kakiese, O.; Maehl, J.H.H.; Mulungo, M.; Nagda, S.M.; Paling, R.W.; Pelo, M.; Rarieya, J.M.; Sheria, M.; Thorpe, W.R.; et al. (1988)
N’Dama cow and calf viabilities, parturition intervals, cow parturition and weaning weights and calf weaning weights were recorded during a three year period, January 1984 to December 1986. The management system was the same at Mushie and Kolo ranches (Zaire) where trypanosomiasis risk was high and zero, respectively. The average calving interval at kolo was about two months (16%) shorter than at Mushie Ranch, the respective means being 426 and 493 days. The corresponding calculated calving percentages were 85.7% for Kolo and 74.0% for Mushie. Live weight performance was better in Kolo than in Mushie for all liveweight characters considered. All the 3 cow productivity indices showed that, cows at kolo were more productive than cows at Mushie. Herd productivity index. The similar productivities of N’Dama cattle at two ranches with contrasting trypanosomiasis risk levels, but which were other wise comparable, confirms that at this level of risk trypanosomiasis is not a major factor affecting the productivity of this trypanotolerant breed.